Pengasuhan Anak Usia Dini Dalam Lensa Fikih: Telaah Kitab Tuḥfatul Maudūd Bi Aḥkāmil Maulūd Karya Ibnu Qayyim Al-Jauziyyah - Ilma, Mughniatul (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to examine the concept of early childhood care in the perspective of fiqh based on the work of Ibn Qayyim al-Jauziyyah entitled Tuḥfatul Maudūd bi Aḥkāmil Maulūd. This book discusses in depth various vital aspects of parenting, ranging from breastfeeding, teething, and learning to walk to the appropriate dress code for them. Based on a normative approach and literature study method, this study explores Ibn Qayyim's thoughts on the phases of child development and ethical and spiritual values that should be instilled early on. The results of this study are expected to provide comprehensive guidance for parents in guiding their children holistically so that they can grow into physically and mentally healthy individuals and have a solid religious foundation.